2012
DOI: 10.9790/0837-0145964
|View full text |Cite
|
Sign up to set email alerts
|

http://www.iosrjournals.org/iosr-jhss/papers/vol1-issue4/H0145964.pdf

Abstract: Abstract:Tuberculosis (TB) is an infectious disease which is transmitted through the air. This disease damages the lungs and other organs in the human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The majority of respondents were uncertain of the spread with many claiming that coughing does not spread TB but contaminated food does. There was also a high level of stigma for anyone affected with TB [51]. The authors found the findings troubling as these university students represent a cohort of highly educated individuals and speculated that the results could be worse in less educated individuals [51].…”
Section: Level Of Educationmentioning
confidence: 97%
“…The majority of respondents were uncertain of the spread with many claiming that coughing does not spread TB but contaminated food does. There was also a high level of stigma for anyone affected with TB [51]. The authors found the findings troubling as these university students represent a cohort of highly educated individuals and speculated that the results could be worse in less educated individuals [51].…”
Section: Level Of Educationmentioning
confidence: 97%